In Vivo Behavior of the Antibacterial Peptide Cyclo[RRRWFW], Explored Using a 3-Hydroxychromone-Derived Fluorescent Amino Acid - Afonin, Sergii; Koniev, Serhii; Préau, Laetitia; Takamiya, Masanari; Strizhak, Alexander V.; Babii, Oleg; Hrebonkin, Andrii; Pivovarenko, Vasyl G.; Dathe, Margitta; le Noble, Ferdinand; Rastegar, Sepand; Strähle, Uwe; et al. (Frontiers in Chemistry, 2021)
Labeling biomolecules with fluorescent labels is an established tool for structural, biochemical, and biophysical studies; however, it remains underused for small peptides. In this work, an amino acid bearing a 3-hydroxychromone fluorophore, 2-amino-3-(2-(furan-2-yl)-3-hydroxy-4-oxo-4H-chromen-6-yl)propanoic acid (FHC), was incorporated in a known hexameric antimicrobial peptide, cyclo[RRRWFW] (cWFW), in place of aromatic residues. Circular dichroism spectropolarimetry and antibacterial activity measurements demonstrated that the FHC residue perturbs the peptide structure depending on labeling position but does not modify the activity of cWFW significantly. FHC thus can be considered an adequate label for studies of the parent peptide. Several analytical and imaging techniques were used to establish the activity of the obtained labeled cWFW analogues toward animal cells and to study the behavior of the peptides in a multicellular organism. The 3-hydroxychromone fluorophore can undergo excited-state intramolecular proton transfer (ESIPT), resulting in double-band emission from its two tautomeric forms. This feature allowed us to get insights into conformational equilibria of the labeled peptides, localize the cWFW analogues in human cells (HeLa and HEK293) and zebrafish embryos, and assess the polarity of the local environment around the label by confocal fluorescence microscopy. We found that the labeled peptides efficiently penetrated cancerous cells and localized mainly in lipid-containing and/or other nonpolar subcellular compartments. In the zebrafish embryo, the peptides remained in the bloodstream upon injection into the cardinal vein, presumably adhering to lipoproteins and/or microvesicles. They did not diffuse into any tissue to a significant extent during the first 3 h after administration. This study demonstrated the utility of fluorescent labeling by double-emission labels to evaluate biologically active peptides as potential drug candidates in vivo.